Valorization of coal fly ash for the synthesis of lithium nickel-cobalt-aluminum-iron oxide (NCAF) cathode material - Yudha, Cornelius Satria; Rahmawati, Aleida Dwi; Sumarti, Ragil; Muzayanha, Soraya Ulfa; Lestari, Annisa Puji; Arinawati, Meidiana (International Journal of Renewable Energy Development, 2025)
This study demonstrates a novel approach to high-performance cathode materials by utilizing coal fly ash as a source of Al and Fe dopants for nickel-rich layered oxides. LiNixCoyAlzFe(1-x-y-z)O2 (NCAF) materials were synthesized through a combined hydrometallurgical-solid state route, incorporating fly-ash waste-derived Al/Fe hydroxides (AFH) at various concentrations during the lithiation process. The characteristics of NCAF precursors, AFH and Ni0.8Co0.2C2O4, were thoroughly investigated. Structural analysis confirms the successful formation of single-phase materials with α-NaFeO2 structure (R-3m) up to 5% AFH content, exhibiting changes in the level of order, lattice parameters, and unit cell volume. Surface area characteristics show a transition from 38.747 m²/g to 6.52 m²/g with increasing AFH content, approaching the ideal surface area. The compositional evolution from LiNi0.8Co0.2O2 to LiNi0.66Co0.16Al0.08Fe0.10O2 maintains uniform atomic distribution. In the full-cell configuration with graphite anodes (N/P ratio: 1.2-1.3), NCAF with 5% AFH demonstrates enhanced electrochemical performance (~155 mAh/g), attributed to synergistic effects of Al-induced structural stabilization and Fe-contributed redox activity. This approach establishes a pathway for simple and low-cost battery material development while addressing industrial waste utilization.